2003
DOI: 10.1159/000067866
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model of Inorganic Phosphorus Mass Balance in Hemodialysis Therapy

Abstract: Background: There is growing evidence that inorganic phosphorus (iP) accumulation in tissues (dTiP/dt) is a risk factor for cardiac death in hemodialysis therapy (HD). The factors controlling iP mass balance in HD are dietary intake (GiP), removal by binders (JbiP) and removal by dialysis (JdiP). If iP accumulation is to be minimized, it will be necessary to regularly monitor and optimize GiP, JbiP and JdiP in individual patients. We have developed a kinetic model (iPKM) designed to monitor these three paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 1 publication
3
54
0
Order By: Relevance
“…Sugasaki et al (21,22) and Gotch et al (35) proposed modified one-compartment models; the former proposed the incorporation of a time- Table 2. Estimated values of patient parameters from short hemodialysis (SHD) and conventional hemodialysis (CHD) sessions dependent phosphorus generation rate, and the latter empirically fit data to an equation derived from a one-compartment model.…”
Section: Discussionmentioning
confidence: 99%
“…Sugasaki et al (21,22) and Gotch et al (35) proposed modified one-compartment models; the former proposed the incorporation of a time- Table 2. Estimated values of patient parameters from short hemodialysis (SHD) and conventional hemodialysis (CHD) sessions dependent phosphorus generation rate, and the latter empirically fit data to an equation derived from a one-compartment model.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies quantifying these important relationships have been reported from the Renal Research Institute in New York [28,29,30,31,32,33,34] but are not often considered in the discussion of the dialysis prescription [1,2,3]. As shown in figure 16 P is widely distributed in all protein-rich foodstuffs and particularly in dairy products.…”
Section: Errors In Delivery Of the Prescribed Cdinamentioning
confidence: 99%
“…Calculation of calcium absorbed and removed with calcium kinetic modeling [for more details, see [28,29,30,31,32,33,34]].…”
Section: Errors In Delivery Of the Prescribed Cdinamentioning
confidence: 99%
“…Ideally, adequate dialysis in any form would remove adequate amounts of all uremic toxins, including phosphorus. Unfortunately, conventional, thrice-weekly hemodialysis (4 h duration) removes approximately 900 mg of phosphorus each treatment (an average of only 300 mg/d) (18). Conventional, intermittent hemodiafiltration improves phosphorus removal modestly (1030 to 1700 mg/treatment) (19), but overall, conventional, intermittent hemodialysis provides inadequate removal of phosphorus.…”
Section: Dialysismentioning
confidence: 99%